Availability of family planning services and quality of counseling by faith-based organizations: a three country comparative analysis - Janine Barden-O'Fallon (BMC, 2017)
Abstract Background Faith-based organizations (FBOs) have a long history of providing health services in developing countries and are important contributors to healthcare systems. Support for the wellbeing of women, children, and families is evidenced through active participation in the field of family planning (FP). However, there is little quantitative evidence on the availability or quality of FP services by FBOs. Methods The descriptive analysis uses facility-level data collected through recent Service Provision Assessments in Malawi (2013-14), Kenya (2010), and Haiti (2012) to examine 11 indicators of FP service and method availability and nine indicators of comprehensive and quality counseling. The indicators include measures of FP service provision, method mix, method stock, the provision of accurate information, and the discussion of reproductive intentions, client's questions/concerns, prevention of sexually transmitted infections, and return visits, among others. Pearson's Chi-square test is used to assess the selected indicators by managing authority (FBO, public, and other private sector) to determine statistical equivalence. Results Results show that FBOs are less likely to offer FP services than other managing authorities (p < 0.05). For example, 69% of FBOs in Kenya offer FP services compared to 97% of public facilities and 83% of other private facilities. Offering long-acting or permanent methods in faith-based facilities is especially low (43% in Malawi, 29% in Kenya and 39% in Haiti). There were few statistically significant differences between the managing authorities in comprehensive and quality counseling indicators. Interestingly, Haitian FBOs often perform as well or better than public sector health facilities on counseling indicators, such as discussion of a return visit (79% of FBO providers vs. 68% of public sector providers) and discussion of client concerns/questions (52% vs. 49%, respectively). Conclusions Results from this analysis indicate that there is room for improvement in the availability of FP services by FBOs in these countries. Quality of counseling should be improved by all managing authorities in the three countries, as indicated by low overall coverage for practices such as ensuring confidentiality (22% in Malawi, 47% in Kenya and 12% in Haiti), discussion of sexually transmitted infections (18%, 25%, 17%, respectively), and providing services to youth (53%, 27%, 32%, respectively).